2021
DOI: 10.1177/03611981211036363
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Ridesplitting Behavior with Interpretable Machine Learning Models Using Chicago Transportation Network Company Data

Abstract: As congestion levels increase in cities, it is important to analyze people’s choices of different services provided by transportation network companies (TNCs). Using machine learning techniques in conjunction with large TNC data, this paper focuses on uncovering complex relationships underlying ridesplitting market share. A real-world dataset provided by TNCs in Chicago is used in analyzing ridesourcing trips from November 2018 to December 2019 to understand trends in the city. Aggregated origin–destination tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Khaloei et al ( 25 ) developed a mixed logit model using data from a stated- and revealed-preference survey conducted in the U.S.A. and found that commuter trips in an autonomous ridehailing environment would likely result in mostly solo ridehailing trips. Abkarian et al ( 26 ) studied Chicago’s TNC trip data from November 2018 to December 2019 and found that shared rides amounted to 20%–30% of all ridesourcing trips throughout the day (implying that ridesplitting choice was not dependent on trip purpose). A study of Didi Chuxing data from November 2016 found that ridesplitting trips were more frequent on weekdays during the middle of the day rather than during the morning or afternoon peak commuting travel period; meanwhile, ridesplitting on weekends was more prevalent for evening trips ( 27 ).…”
Section: Factors Affecting the Choice Of Poolingmentioning
confidence: 99%
See 1 more Smart Citation
“…Khaloei et al ( 25 ) developed a mixed logit model using data from a stated- and revealed-preference survey conducted in the U.S.A. and found that commuter trips in an autonomous ridehailing environment would likely result in mostly solo ridehailing trips. Abkarian et al ( 26 ) studied Chicago’s TNC trip data from November 2018 to December 2019 and found that shared rides amounted to 20%–30% of all ridesourcing trips throughout the day (implying that ridesplitting choice was not dependent on trip purpose). A study of Didi Chuxing data from November 2016 found that ridesplitting trips were more frequent on weekdays during the middle of the day rather than during the morning or afternoon peak commuting travel period; meanwhile, ridesplitting on weekends was more prevalent for evening trips ( 27 ).…”
Section: Factors Affecting the Choice Of Poolingmentioning
confidence: 99%
“…Most research looking at data on race and ethnicity in ridesourcing tends to show that non-white persons are more likely to choose a ridepool option than non-Hispanic/Latinx white populations. Studies of shared TNC trip data in Chicago from 2019 using advanced statistical models and machine learning techniques to estimate sharing decisions in TNC trips found that census tracts with higher percentages of non-white persons were positively associated with having shared rides occur in those neighborhoods and that the proportion of the white population at the drop-off area was negatively correlated with ridesplitting ( 26 , 29 ). Meanwhile, the 2019 Austin survey analysis using a joint RP-SP model ( 35 ) found that non-Hispanic/Latinx whites had a lower propensity to choose pooled rides.…”
Section: Factors Affecting the Choice Of Poolingmentioning
confidence: 99%
“…This model integrates passenger-vehicle matching and vehicle routing optimization. It not only optimizes order allocation, but also takes into account the impact of cost growth and profit reduction caused by passengers' route differences, so it is more practical and significant (23)(24)(25). However, this kind of model usually assumes that all vehicles have a common starting and ending station, which is different from the random spatial position of vehicles in practice.…”
mentioning
confidence: 99%
“…Surge pricing is discussed within the classic economic theory on supply and demand dynamics, as well as other factors such as traffic conditions and trip length. For WTS behavior, recent behavior studies have yielded inconsistent conclusions on the factors governing the behavior (9)(10)(11), for example, travel impedance versus sociodemographic features, although they used the same data from the same geography and for the same period to analyze and model the behavior. One can attribute these inconsistent results to the difference in the granularity level of the analysis, that is, community level as opposed to census tract level.…”
mentioning
confidence: 99%